PJMHS 2022
DOI: 10.53350/pjmhs20221611687
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Etiology of Zygomatic Complex Fractures in Oral and Maxillofacial Trauma Patients in Tertiary Care Hospital Karachi

Abstract: Aim: To determine the frequency and etiology of zygomatic complex fractures in oral and maxillofacial trauma patients. Methods: This cross sectional study was conducted at Oral and Maxillofacial department on 116 patients presenting with oral and maxillofacial trauma. Frequency and etiology of zygomatic complex fractures in these patients were determined. Frequencies and percentages were used for categorical data while mean and SD was calculated for numerical data. Chi Square test for applied for association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Various studies revealed higher incidence of ZMC fracture in male population ranging from 65-95%. [1][2][3][4]11 This may be due to involvement of male in outdoor activities related to jobs, sports, violence and substance abuse etc. 74.43%) in their study, which might be due to over speeding, non-enforcement of traffic laws, unplanned urbanization, not wearing protective gear.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Various studies revealed higher incidence of ZMC fracture in male population ranging from 65-95%. [1][2][3][4]11 This may be due to involvement of male in outdoor activities related to jobs, sports, violence and substance abuse etc. 74.43%) in their study, which might be due to over speeding, non-enforcement of traffic laws, unplanned urbanization, not wearing protective gear.…”
Section: Resultsmentioning
confidence: 99%
“…4,17 Epistaxis is mainly due to nasal injury which is most common associated loco regional injury in this study and nasal bone fracture is most common facial bone fracture followed by ZMC fracture. 2,6,9,18,19 Epistaxis may also result from sinus bleeding for which proper evaluation and management is needed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations